2018
DOI: 10.3390/mi9060259
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multiple Capsule Robots in Pipe

Abstract: Swallowable capsule robots which travel in body cavities to implement drug delivery, minimally invasive surgery, and diagnosis have provided great potential for medical applications. However, the space constraints of the internal environment and the size limitations of the robots are great challenges to practical application. To address the fundamental challenges of narrow body cavities, a different-frequency driven approach for multiple capsule robots with screw structure manipulated by external electromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A capsule robot (CR) is a noninvasive device that can perform gastrointestinal treatment and comprehensive diagnosis by actively moving, which offers remarkable advantages over traditional endoscopes, such as less trauma, straightforward operation, and no pain for the patient [1][2][3][4]. Energy supply is a severe bottleneck restricting the CR development in the realistic scenario [5].…”
Section: Introductionmentioning
confidence: 99%
“…A capsule robot (CR) is a noninvasive device that can perform gastrointestinal treatment and comprehensive diagnosis by actively moving, which offers remarkable advantages over traditional endoscopes, such as less trauma, straightforward operation, and no pain for the patient [1][2][3][4]. Energy supply is a severe bottleneck restricting the CR development in the realistic scenario [5].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 , 19 ] Magnetic robots have also been studied for group tasks, such as assembly, but most of the work at milli/centimeter and smaller scales do not focus on enhancing the electrical capacity beyond individual modules, and enhancement of electrical operations by groups are mostly seen in magnetic modules of larger scales, where the energy storage is a relatively less significant problem or in cases where electrical power is provided by external wires. [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] For example, it has been demonstrated that small magnetic modules can serve as connection conductors for an existing electronic circuit or they can be used in the placement of components for intra‐modular or module‐to‐substrate assembly. [ 37 , 38 , 39 ] Nevertheless, the question of obtaining long‐duration powers and functionalities exceeding single module capacities for the completed electronic circuits still remains when the completed circuits are desired to be wireless and mobile.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal micro-robot is currently a hotspot in the field of the endoscope medical equipment [1][2][3][4]. It can actively moves in gastrointestinal tract and performs comprehensive diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%